Social information retrieval systems emerging technologies and applications for searching the Web effectively - Goh, Dion; Foo, Schubert (Gale virtual reference library, 2008)
"Provides relevant content in the areas of information retrieval systems, services, and research; covering topics such as social tagging, collaborative querying, social network analysis, subjective relevance judgments, and collaborative filtering. Answering the increasing demand for authoritative resources on Internet technologies, this will make an indispensable addition to any library collection"--Provided by publisher.